Impact of primary dentition malocclusion on the oral health-related quality of life in preschoolers - Fernanda Marques Torres de Vasconcelos (SpringerOpen, 2021)
Abstract Background Malocclusion is a condition frequently seen in primary dentition due to the interaction of environmental, genetic and behavioural factors. The occurrence of some types of malocclusions can have an impact on oral health-related quality of life in children. Hence, the present study aimed to verify the impact of primary dentition malocclusion on oral health-related quality of life in preschool children. Methods A population-based cross-sectional study was conducted in Florianopolis, Brazil, with a representative sample of 1050 preschoolers aged between 2 and 5 years, randomly selected. Parents answered the Brazilian version of the Early Childhood Oral Health Impact Scale and also to a questionnaire on socio-economic indicators. Data obtained from the questionnaire were obtained by item response theory based on model of gradual response. The malocclusion assessed was: anterior open bite, increased overjet and posterior crossbite. Poisson regression model was employed for multivariate analysis (P < 0.05). Results Malocclusion was observed in 36.7% of the children. Of these, 11.4% were anterior open bite, 67.2% were increased overjet, and 21.4% were posterior crossbite. Malocclusion's impact on oral health-related quality of life was 28.6%. In children aged 4–5 years, the prevalence of malocclusion’s impact on quality of life was 49.5% higher than in children aged 2–3 years. Statistical analysis showed that preschool children with malocclusion showed no significant impact on quality of life. Conclusions The findings of the present study indicate that the occurrence of primary dentition malocclusion has no impact on the quality of life of children aged 2–5 years.